Traditional chinese medicine in coronary microvascular disease - Yang, Zhihua; Lin, Shanshan; Liu, Yangxi; Ren, Qiuan; Ge, Zhao; Wang, Ci; Bi, Yingfei; Wang, Xianliang; Mao, Jingyuan (Frontiers in Pharmacology, 2022)
Coronary microvascular disease (CMVD) is common in patients with cardiovascular risk factors and is associated with an increased risk of adverse cardiovascular events. Although the study of CMVD in modern medicine is going on, there is still no effective treatment for it. Traditional Chinese medicine (TCM) has some clinical advantages based on syndrome differentiation and individualized treatment. In this review, we reviewed the clinical significance, pathogenesis, and current treatment of CMVD, and systematically summarized the clinical efficacy and potential action mechanisms of TCM for CMVD. In addition, the scientific problems to be solved urgently and the research strategy of TCM for CMVD were put forward. CMVD is of great clinical significance, but there are still many gaps in the related research. The aim of this review is to draw the attention of clinicians to CMVD and to promote research on CMVD in TCM.